Lucy's new friend - Ross, Thea, 1949- (Hauppauge, N.Y. : Parklane Pub., 2005)
Lucy is lonely. When she goes to the park she meets a dog named Sally and they become friends.
On board pages.
Title from cover.
Keywords: Dogs -- Juvenile fiction; Dogs